Traffic deaths: recent evolution and regional differences in Bahia State, Brazil - Polianna Alves Andrade Rios; Eduardo Luiz Andrade Mota (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study describes the temporal evolution of mortality due to traffic accidents in regions within Bahia State, Brazil, from 1996 to 2007, using data from the Brazilian Mortality Information System. We calculated overall rates of mortality due to traffic accidents and specific rates by type of victim. Temporal evolution was analyzed by means of correlations between rates and years of study, as well as polynomial regression models to evaluate trends. During the study period, the regions analyzed accounted for 60% of deaths due to traffic accidents in Bahia. Excess mortality among males and superior percentage of deaths in young individuals were observed. Overall, the evolution of global rates showed decreases beginning in 1998, but growth resumption in 2000, although the trend was not statistically significant. Regional differences were more marked when analyzing rates according to type of victim. However, a growing trend was observed in most locations for rates of accidents involving motorcyclists, which, in conjunction with other findings, substantiates concerns regarding the current situation of increased deaths involving motorcycles in Brazil.